Rivaroxaban Suppresses Atherosclerosis by Inhibiting FXa-Induced Macrophage M1 Polarization-Mediated Phenotypic Conversion of Vascular Smooth Muscle Cells - Ma, Yanpeng; Zhang, Yong; Qiu, Chuan; He, Chunhui; He, Ting; Shi, Shuang; Liu, Zhongwei (Frontiers in Cardiovascular Medicine, 2021)
Background: Factor Xa (FXa) is a mediator initiating and accelerating atherosclerosis (AS). Both macrophage and vascular smooth muscle cells (VSMCs) participate in AS progression. This study was aimed to investigate the mechanisms underlying the effects of the FXa inhibitor rivaroxaban on AS. Methods: Rivaroxaban was administrated to AS mice. Primary macrophages were exposed to FXa, treated with rivaroxaban and transfected with siRNA silencing protease-activated receptor 2 (PAR2), hypoxia-inducible factor 1α (HIF1α), delta-like receptor 4 (Dll4), and Akt. Interaction between macrophages and VSMCs was assessed by co-culturing systems. Atherosclerotic lesions were evaluated by oil red O stain. Fluorescent staining was used to determine the cell phenotypes. Secretion of inflammatory cytokines and collagen were assessed by ELISA and Sircol assays. Western blotting was used to evaluate the protein expression and phosphorylation levels. Results: Rivaroxaban reduced lesion area, M1 macrophages accumulation and VSMCs contractile- synthetic phenotypic conversion in atherosclerotic plaques. FXa exposure induced macrophages polarization toward M1 and Dll4 high expression, which were inhibited by PAR2, Akt1 and HIF1α silencing. Rivaroxaban treatment inhibited PAR2/Akt/HIF1α signaling activation and Dll4 expression in FXa- exposed macrophages. By cell-to-cell contact, M1 macrophages induced Notch signaling activation in VSMCs which committed contractile- synthetic conversion. Rivaroxaban treatment and Dll4 silencing incapacitated macrophage in inducing VSMCs phenotypic conversion upon cell-to-cell contact. Conclusion: Rivaroxaban suppresses atherosclerosis by inhibiting FXa- induced PAR2/Akt/HIF1α signaling activation- mediated macrophage M1 polarization and high Dll4 expression. These macrophages facilitated VSMCs to perform contractile- synthetic phenotypic conversion upon macrophage- VSMCs cell-to-cell contact.